Exploring Factors Influencing Technology Adoption among Generation Y: A Study of MOOC Users - Gemintang Sukma Alnisa Dhewandrie; Ahyar Yuniawan (University of Merdeka Malang, 2023)
The primary objective of this study is to investigate the factors affecting customers’ intention and usage of MOOC (Massive Open Online Course) in generation Y based on the UTAUT 2 (Unified Theory of Acceptance and Use of Technology 2). The paper opted for a quantitative method involving 150 MOOC (Skill Academy and My Skill) users collected by spreading an online questionnaire through social media. The data analysis method used is PLS-SEM. The results show that performance expectations, effort expectations, social influence, facilitating conditions, price values, and habitss have a positive influence on behavioral intention. However, hedonic motivation does not appear to have a significant effect on behavioral intention. Then behavioral intention has a significantly positive influence on usage behavior